The Influence of Aiesec Global Volunteer Activities Towards Students’ Speaking Confidence - Mely Yanti; Clarry Sada; Urai Salam (Kirana Publisher (KNPub), 2023)
This study aims to describe how the activities done by the learners when they were having the Global Volunteer Program in AIESEC can influence students speaking confidence and to explain why those activities, can contribute to the improvement of learners’ speaking confidence. This research is a qualitative case study. The subjects of this research were three participants who experienced the program of AIESEC Global Volunteer. This research was done by interviewing all the participants and collecting artifacts from the program. The result of this research was that all participants appeared to be so confident in answering the interview questions and expressing themselves. Besides, all the participants stated that the program of AIESEC Global Volunteer Activities indeed brought their confidence to the next level. In other words, during the program, they experienced so many pieces of training that it was believed that those activities contributed to the improvement of their speaking confidence.